Curriculum Management and Physics Learning at Madrasah Aliyah (MA) Islamic Modern Islamic Boarding School (PPMI) Assalaam Surakarta - Muchamad Soleh Pratono; Maryadi Maryadi; Djumadi Djumadi (CV. Rayyan Dwi Bharata, 2023)
The purpose of this research is to explain: (1) curriculum and learning planning. (2) organizing curriculum and learning. (3) implementation of curriculum and learning. (4) evaluation of the implementation of curriculum and learning. This type of research is a qualitative research with an ethnographic design that was carried out at the Madrasah Aliyah PPMI Assalaam Surakarta. Data collection techniques with in-depth interviews, documentation, and observation. Data analysis uses an interactive analysis model with three stages. The results of the study were (1) Learning planning, in the preparation of madrasa curriculum documents a curriculum development team was formed involving all elements of the madrasa to verify syllabus documents, prota and promissory notes, and lesson plans prepared by the teacher before being validated by the head of the madrasa. The final product of the lesson plan is in the form of a KTSP document which is the official madrasah curriculum document as a reference in carrying out teaching and learning activities for one academic year. (2) Organizing Learning, including preparing an educational calendar. Arrangement of teacher assignments according to qualifications and competencies, preparation of lesson schedules assisted by application software. (3) Implementation of learning, including learning objectives, subject matter, methods, media, and evaluation of learning, is a part that must be fulfilled so that the objectives of learning can be achieved. (4) Evaluation of learning implementation, including supervision of learning planning, supervision of learning implementation, and supervision of learning outcomes.